Psychological Well-Being and Self-Esteem in Older Adults Participating in Educational and Recreational Activities in the Municipality of La Paz (Docentes 2.0 Journal, 2025)
The aging process involves physical, emotional, and social changes that can affect the well-being and self-esteem of older adults. This research aimed to analyze the relationship between self-esteem and psychological well-being in older adults who participate in educational and recreational activities organized by the municipality of La Paz. The research was conducted under a positivist paradigm, using a quantitative approach, with a non-experimental, descriptive, and cross-sectional design. The population consisted of adults over 60 residing in La Paz and participating in municipal activities over the past two years. The final sample consisted of 69 participants. The Rosenberg Self-Esteem Questionnaire and the Goldberg Mental Health Scale were administered to collect data, which were analyzed using Excel and SPSS. The results showed that most participants had high levels of self-esteem, particularly in the 60- to 69-year-old age group. This high self-esteem was associated with a lower incidence of anxiety and depression. However, it was observed that emotional disorders were significant in those with average self-esteem levels. It was concluded that participation in recreational activities positively affects self-esteem and the psychological well-being of older adults. However, it does not act as an absolute protective factor against emotional disorders. The results underscore the need to implement public policies and specific programs to strengthen self-esteem and reduce anxiety and depression in this population.
Keywords: Self-esteem; older adults; psychological well-being; recreational activities; anxiety